(untitled) (Iranian Journal of Kidney Diseases, 2009)
Brucellosis is a multisystem disease that may present with a broad spectrum of clinical manifestations. The most frequent symptoms are constitutional symptoms. While involvement of the bones, joints, and liver is not rare, brucellosis may rarely involve the kidney. We present a case of brucellosis with hepatitis, pancytopenia, peripheral arthritis, and kidney failure.